Understanding and responding to climate change in the great plains: source, impact, and mitigation - Rice, Charles W.; Feddema, Johannes; Harrington, John A., Jr.; Hutchinson, Stacy L.; Ma, Chunseng (Kansas State University, 2010)
Several Kansas researchers have been at the forefront of climate science research internationally. This panel discussion will feature some of those researchers as they discuss some of the lessons learned for Kansas as well as next steps internationally, nationally, and in Kansas. They will also discuss the role and importance of higher education in knowledge production and dissemination about climate risks and trends. Finally, they will also comment on how higher education could improve its response to these issues.
Keywords: Climate change; Energy